Defisiensi dan Toksisitas Hara Magnesium Tanaman Padi Gogo (Oryza Sativa L.) Pada Lapisan Tanah Subsoil - Bonardo Vebry Munthe; Irwan Agusnu Putra; Dedi Kurniawan (Universitas Kadiri, 2022)
In increasing the production and quality of rice plants, it is essential to pay attention to proper nutrient management. One of the most important nutrients in increasing rice production and quality is magnesium, tested with deficiency and toxicity treatments in subsoil soils. This study used a factorial randomized block design with two factors where each treatment was repeated three times. First factor included Nutrient toxicity Mg, T0 = 0 (control), T1 = 2.2 g/polybag, T2 = 4.4 g/polybag, T3 = 8.8 g/polybag. Second factor included Mg nutrient deficiency D0 = 0 (control), D1 = 0.56 g/polybag, D2 = 0.28 g/polybag, and D3 = 0.14 g/polybag. The results showed that the deficiency treatment significantly affected plant height 5-6 weeks after fertilization and leaf chlorophyll 9 WSP. In contrast, the toxicity treatment significantly affected Total Chlorophyll 4 MSP and 1000 grain weight, where the D2 and T2 treatments showed the highest data. This study explained that the D2 and T2 treatments showed good plant responses. The red sigambiri variety was quite tolerant of magnesium deficiency and toxicity treatments.